Farmers’ and Herders’ Perceptions on Rangeland Management in Two Agroecological Zones of Benin - Diogo, Rodrigue Vivien cao; DOSSA, HIPPOLYTE GBÉNAKPON LUC HIPPOLYTE; VANVANHOSSOU, FRIDAIUS ULRICH SEYI; ABDOULAYE, Badirou dine; DOSSEH, KOSSI Elliot; HOUINATO, MARCEL ROMUALD BENJAMIN; Schlecht, Eva; Buerkert, Andreas (My University, 2021)
The sustainable use of rangelands in pastoral areas requires the inclusion of all stakeholders to develop sound management strategies. However, the role of these actors in the sustainable management of natural resources is still poorly understood. The present study aims to (i) assess the perception of farmers and herders of the risks and opportunities of transhumance on rangeland resource use and management, and to (ii) generate useful knowledge for the design and implementation of policies that favor the coexistence of these actors and reduce competition over rangeland resources use in Benin. To this end, interviews were conducted with 240 crop farmers and herders using a semi-structured questionnaire in two contrasting agroecological zones in the northern (Kandi) and the southern (Kétou) part of the country. Among the respondents, 64% of farmers in the North were agro-pastoralists (owning 10.6 ha of land and 10.7 cattle) and 36% were herders (keeping 45.8 cattle and cultivating about 3.7 ha of land). They perceived that communal rangelands were entirely degraded. In the South, 36% of respondents were agro-pastoralists (with 0.3 cattle and farming 4 ha of land) and 64% cattle herders (raising 45.3 cattle and farming 0.9 ha of land only). Of the herders, 50% kept cattle for more than 20 years, while agro-pastoralists had no previous experience in cattle herding. Cultivation practices among crop farmers, such as high use of mineral fertilization (23.8%) and bush fires for land clearing (22.5%), were reported in Kandi (North) and Kétou (South) as factors that might contribute to land degradation. However, these farmers perceived transhumance as a threat to the sustainable use of natural resources. In contrast, herders perceived transhumance as an opportunity to valorize unused land and increase the availability of manure to cropland. The prevalent negative attitude of crop farmers regarding transhumant herders increases the vulnerability of cattle herding in both regions. There is an urgent need of raising awareness concerning the mutual benefits provided by the coexistence of crop farmers with herders to promote participative rangeland management strategies. This may contribute towards coping with the current challenges of food insecurity and increasing climate variability as well as to reducing recurrent conflicts in the region
Keywords: communal grazing areas; herder-farmer conflicts; herd mobility; land property rights; rangeland degradation; West Africa